1969
DOI: 10.1111/j.1532-5415.1969.tb03169.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Skeletal Mass and Fragility With Castration in the Rat: A Model of Osteoporosis*

Abstract: Skeletal calcium content was measured in 99 normal and 65 castrated male and female rats. The breaking load in compression of the femur and humerus was measured and the femur-breaking stress calculated. Weight of muscle on the hindlimbs, and the volume and density of the femur were determined.Normal female rats have a greater skeletal calcium content than males, and stronger long bones relative to body weight. This is because bone volume is greater in females compared to males at the same body weight. Castrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1
3

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(52 citation statements)
references
References 9 publications
1
47
1
3
Order By: Relevance
“…The increase curve of body weight in females was different from that of males; the body weight in males increased until 12 months and then reached a plateau (about 400 g), whereas that in females continued to increase to about 300 g (Fig. 1), but our data showed that the BMD values in females were also higher than those in males, as observed in Charles River CD rats aged 23~150 days after birth by Saville [28]. Wronski et al [35] have reported that bone loss is induced regardless of the increase in body weight after ovariectomy, although the tendency to slightly increase bone volume is observed partly in the metaphyses of long bones.…”
Section: Discussioncontrasting
confidence: 50%
“…The increase curve of body weight in females was different from that of males; the body weight in males increased until 12 months and then reached a plateau (about 400 g), whereas that in females continued to increase to about 300 g (Fig. 1), but our data showed that the BMD values in females were also higher than those in males, as observed in Charles River CD rats aged 23~150 days after birth by Saville [28]. Wronski et al [35] have reported that bone loss is induced regardless of the increase in body weight after ovariectomy, although the tendency to slightly increase bone volume is observed partly in the metaphyses of long bones.…”
Section: Discussioncontrasting
confidence: 50%
“…It is well known that rats develop osteopenia after ovariectomy (OVX),' and the OVX rat has been used as a model for postmenopausal osteoporosis (1)(2)(3). Our studies have shown that bone density in rats is reduced 6 mo post-OVX, and that the ratio of femoral cortical thickness to midshaft diameter was significantly lower than normal (x-ray femoral score; Table I).…”
Section: Introductionmentioning
confidence: 72%
“…Ovariectomy (Ovx)' induces osteoporosis in rats ( 12,13) by increasing bone turnover ( 14,15) and the rat has been successfully used as an animal model for postmenopausal osteoporosis (16,17). Estrogen prevents bone loss in this animal model by reducing bone turnover (18)(19)(20)(21)(22) while PTH, given intermittently, acts as an anabolic agent for bone formation (23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%